SARS-CoV-2 viability on different surfaces after gaseous ozone treatment: a preliminary evaluation. (April 2021) - Percivalle, E.; Clerici, M.; Cassaniti, I.; Vecchio Nepita, E.; Marchese, P.; Olivati, D.; Catelli, C.; Berri, A.; Baldanti, F.; Marone, P.; Bruno, R.; Triarico, A.; et al.
Summary: COVID-19 is a global health threat with a huge number of confirmed cases and deaths all over the world. Human-to-human transmission via respiratory droplets and contact with aerosol-infected surfaces are the major routes of virus spread. Because SARS-CoV-2 can remain in the air and on surfaces from several hours to several days, disinfection of frequently touched surfaces and critical rooms, in addition to observing individual hygiene tips, is required to reduce the virus spreading. Here we report on an investigation into the use of gaseous ozone as a potentially effective sanitizing method against the new coronavirus.